Environmental correlates of crimean-congo haemorrhagic fever incidence in Bulgaria - Vescio Fenicia M; Busani Luca; Mughini-Gras Lapo; Khoury Cristina; Avellis Luca; Taseva Evgenia; Rezza Giovanni; Christova Iva (BMC, 2012)
Abstract Background Crimean-Congo Haemorrhagic Fever (CCHF) is a zoonotic viral disease transmitted by ixodid tick bites, mainly of Hyalomma spp., or through contact with blood/tissues from infected people or animals. CCHF is endemic in the Balkan area, including Bulgaria, where it causes both sporadic cases and community outbreaks. Methods We described trends of CCHF in Bulgaria between 1997 and 2009 and investigated the associations between CCHF incidence and a selection of environmental factors using a zero-inflated modelling approach. Results A total of 159 CCHF cases (38 women and 121 men) were identified between 1997 and 2009. The incidence was 0.13 cases per 100,000 population/year with a fatality rate of 26%. An epidemic peak was detected close to the Turkish border in the summer of 2002. Most cases were reported between April and September. Increasing mean temperature, Normalized Difference Vegetation Index (NDVI), savannah-type land coverage or habitat fragmentation increased significantly the incidence of CCHF in the CCHF-affected areas. Similar to that observed in Turkey, we found that areas with warmer temperatures in the autumn prior to the case-reporting year had an increased probability of reporting zero CCHF cases. Conclusions We identified environmental correlates of CCHF incidence in Bulgaria that may support the prospective implementation of public health interventions.